Unlocking the power of metacognition in mathematically gifted minds - Erdoğan, Fatma (Genç Bilge Yayıncılık, 2025)
The aim of this study is to critically examine the importance of metacognitive skills in the problem-solving processes of mathematically gifted students and to evaluate the relevant literature. The study explores how these students utilize skills such as planning, monitoring, and evaluation, as well as the relationship of these skills to academic achievement and their contribution to the learning process. Furthermore, these competencies are considered from cognitive, psychological, and pedagogical perspectives. Research has shown that mathematically gifted students are able to use metacognitive processes such as planning, monitoring, and evaluation more effectively and flexibly. These students not only reach correct solutions but also demonstrate a high level of awareness regarding the problem-solving process, enabling them to restructure their strategies when necessary. Therefore, mathematically gifted students distinguish themselves from their peers not only through their numerical abilities but also through their advanced metacognitive capacities. However, it has also been noted that heightened metacognitive awareness may occasionally lead to challenges such as over-analysis, perfectionism, or emotional sensitivity. Hence, in supporting gifted students, it is essential to consider their emotional and psychological development alongside their cognitive growth. In conclusion, for mathematically gifted students to fully realize their potential, it is essential to support not only their high-level cognitive abilities but also their metacognitive strategies in a holistic manner. Such support not only enhances academic achievement but also strengthens long-term learning habits, self-efficacy, and motivation for problem-solving. Structuring educational environments in ways that encourage the development of these skills will contribute to the formation of more productive and well-balanced individuals within this student group.
Keywords: Special Talented Education; Özel Yetenekli Eğitimi